Interiority in Sade Village Indigenous Corridor - Kusumowidagdo, Astrid; Rahadiyanti, Melania; Utomo, Tri Noviyanto Puji (Interiority, 2023)
This study aims to find and define interiority as an initiative to preserve culture and traditions in Sade Village, Lombok Island, a tourist area in Indonesia. This study adopted qualitative research with the case study method, recording several data sources through field observation, literature studies, archives, and in-depth interviews with community leaders. This study identifies the typology of areas that create psychological, form-based, atmospheric, and programmatic interiority (Teston, 2020) in various configurations. This study found the types of interiorities in Sade Village that contribute to the corridor’s uniqueness, visitors’ feeling of insideness, and the area’s maintenance. Five categories of interiority, namely psychological, form-based, atmospheric, programmatic, and narrative interiority were found in the corridor of Sade Village. The finding on narrative interiority refers to the philosophy of social life of the local community, producing interiority by the meaningful ancient tradition and local beliefs. This study would contribute to increasing awareness of the inherent cultural values of Sade Village to strengthen the image of the area and its tourism potential.